The Interplay Between Stress, Inflammation, and Emotional Attention: Relevance for Depression - Maydych, Viktoriya (Frontiers in Neuroscience, 2019)
Depression is among the most significant public mental health issues. A growing body of research implicates elevated levels of inflammatory markers (e.g., IL-1β, IL-6, and TNF-α) in the etiology and pathophysiology of depression. Yet, the results are somewhat inconsistent, leading to burgeoning attempts to identify associations between inflammation and specific symptoms of depression, including attention to emotional information. Negative attention bias, defined as a tendency to direct attention toward negatively valenced information, is one of the core cognitive features of depression and is reliably demonstrated in depressed and vulnerable individuals. Altered attentional processing of emotional information and immunological changes are often precipitated by stressful events. Psychological stress leads to elevated levels of pro-inflammatory cytokines and cognitive-affective changes that play a critical role in the onset, maintenance, and recurrence of depression. Using various designs, recent studies have reported a positive relationship between inflammation and negative attention bias on behavioral and neural levels, suggesting that the association between inflammation and emotional attention might represent a neurobiological pathway linking stress and depression. This mini review summarizes current research on the causal (bidirectional) relationships between different types of stressors, emotional attention, inflammation, and depression, and discusses potential neurobiological mechanisms underlying these interactions. The integration provided aims to contribute toward understanding how biological and psychological processes interact to influence depression outcomes.